Modeling a pumped storage power integration to a hybrid power system with solar-wind power and its stability analysis. (February 2019) - Xu, Beibei; Chen, Diyi; Venkateshkumar, M.; Xiao, Yu; Xing, Yanqiu
Abstract: Global primary energy consumption will continue to increase with a high rate to 2050, which will be a big challenge for countries to meet both global and regional energy demand. Pumped storage stations (PSS) integrated to a hybrid power system (HPS) with solar and wind power for China are under construction to tussle with this challenge. Historically, modeling of a PSS integrated HPS has been ignored the interaction effect between the shaft vibration and the governing strategies, which will increase the dynamic risk of PSS disconnected immediately to HPS. Here we unify the models of the hydro-turbine governing system and hydro-turbine generator units with a novel expression of hydraulic forces. We quantize all the parameter's interaction contributions of PSS integration to HPS and validate this model with the existing models. Finally, we show the feasibility of PSS's model in integrating of a HPS under steady and fault scenarios.